2019
DOI: 10.1016/j.eurox.2019.100043
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific anti-Mullerian hormone (AMH) levels poorly affects cumulative live birth rate after intra-uterine insemination

Abstract: Objective To evaluate the impact of age-specific anti-Mullerian (AMH) levels on the cumulative live birth rate after 4 intra uterine inseminations (IUI). Study Design The retrospective study study involved 509 couples who underwent their first IUI between January 2011 and July 2017 in the Toulouse University Hospital. All IUI were performed after an ovarian stimulation combining recombinant FSH and GnRH antagonist. The main measure outcome was the cumulative live birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 44 publications
4
12
0
Order By: Relevance
“…17 However, it is well known that AMH levels are strongly correlated with age. 18 This study demonstrates herein that AMH was a statistically significant predictor of yield utilising univariate analysis, but when controlling for other variables using multivariate analysis, no significant relationship was identified. We propose therefore, that when assessing oocyte yield controlling for confounders such as age; such interrelationships may nullify the impact of AMH.…”
Section: Discussionmentioning
confidence: 71%
“…17 However, it is well known that AMH levels are strongly correlated with age. 18 This study demonstrates herein that AMH was a statistically significant predictor of yield utilising univariate analysis, but when controlling for other variables using multivariate analysis, no significant relationship was identified. We propose therefore, that when assessing oocyte yield controlling for confounders such as age; such interrelationships may nullify the impact of AMH.…”
Section: Discussionmentioning
confidence: 71%
“…AMH is considered a reliable predictor of oocyte yield [ 17 ]. However, it is well reported that levels are strongly correlated with age [ 18 ]. Although this study demonstrates AMH was a statistically significant predictor of yield from univariate analysis, there was no significant relationship when controlling for confounding variables with multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the prognosis of IUI cycles is inferior compared to that of non-male factor couples because of the lower quality and quantity of inseminated spermatozoa. 16 Moreau et al 6 evaluated the livebirth rate after four IUI cycles in a retrospective study. They concluded that age-specific levels of AMH were not associated with the cumulative livebirth rate irrespective of age groups; a 9%-12% birth rate after four IUI was observed in women with low AMH.…”
Section: Discussionmentioning
confidence: 99%